10 сказок малышам: [для чтения родителями детям] / Владимир Степанов ; [редактор Т. Рашина] - Степанов Владимир Александрович (Читаем детям, 2015)
Экземпляры: аб. ДБ (2017.20.12) / Инвентарный номер: 3828 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 79 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6